2015
DOI: 10.1053/j.jrn.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Supplementation Lowers Plasma p-Cresol in Chronic Kidney Disease Patients

Abstract: Objective To determine the effects of supplemental fiber on plasma p-cresol, stool frequency, and quality of life (QoL) in chronic kidney disease (CKD) patients. Design and Setting In a 12-week single-blind study, participants were provided with control muffins and supplements (5.5 g sucrose/day) for 2 weeks, muffins containing 10 g/day pea hull fiber and control supplements for 4 weeks, and muffins with 10 g/day pea hull fiber and 15 g/day inulin as a supplement for 6 weeks. Subjects Individuals with CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 31 publications
1
64
0
3
Order By: Relevance
“…In each of these studies, the acceptance of foods with added pea hull fiber was demonstrated by compliance. In the study with children, compliance with consumption of the snacks with added pea hull fiber was 77% versus 74% for the control snacks (18), whereas in the CKD study compliance with consumption of the muffins with added pea hull fiber was 92% versus 97% for the control muffins (42). In the long-term care study, no change in food intake was reported with the pea hull fiber intervention, suggesting the added pea hull fiber was acceptable (9).…”
Section: Effects Of Pea Hull Fiber On Gut Microbiotamentioning
confidence: 98%
See 1 more Smart Citation
“…In each of these studies, the acceptance of foods with added pea hull fiber was demonstrated by compliance. In the study with children, compliance with consumption of the snacks with added pea hull fiber was 77% versus 74% for the control snacks (18), whereas in the CKD study compliance with consumption of the muffins with added pea hull fiber was 92% versus 97% for the control muffins (42). In the long-term care study, no change in food intake was reported with the pea hull fiber intervention, suggesting the added pea hull fiber was acceptable (9).…”
Section: Effects Of Pea Hull Fiber On Gut Microbiotamentioning
confidence: 98%
“…However, inulin has not been shown to affect stool frequency in similarly sized trials (4,45), and thus, pea hull fiber, which is high in insoluble fiber, may have exerted this effect. In a small trial of adults with CKD, providing 1 muffin containing 10 g of pea hull fiber per day resulted in a significant increase in stool frequency (42). It is notable that when 15 g of inulin was provided as a supplement in addition to the pea hull fiber, no further increase in stool frequency was observed.…”
Section: Effects Of Pea Hull Fiber On Gut Microbiotamentioning
confidence: 98%
“…Such epidemiological data should be interpreted with caution, however, as there is some uncertainty about whether dietary fibre per se is beneficial or whether other nutrients, including antioxidant compounds that are present in fibre-rich foods, act in a beneficial manner [52]. Interventions that have focused on increasing total dietary fibre intake in patients with pre-dialysis CKD have reported reductions in serum creatinine levels [53] and plasma p-cresol [54]. A four-week study in which patients with chronic renal failure consumed 50 grams per day of acacia gum, a highly fermentable fibre, led to a mean reduction in plasma urea of 12% [55].…”
Section: Dietary Fibre/non Digestible Carbohydratesmentioning
confidence: 99%
“…However, to date, no clinical trial has evaluated the association between changes in the microbiota and the decrease in colonderived uremic toxins after prebiotic therapy in CKD. The few short-term prebiotic interventions performed so far have reported mixed effects on PCS and IS [131,[135][136][137][138]. The reasons for the heterogeneity in the results may be related to differences in type and amount of prebiotic used, factors that might be relevant for modulation of serum PCS and/or IS in CKD (Table 1).…”
Section: Gut Ecosystem In Ckd and Immunitymentioning
confidence: 99%